New polishing concepts for optical components in flexible and efficient process chains - Bliedtner Jens; Faehnle Oliver; Henkel Sebastian; Schulze Christian; Frank Samson (EPJ Web of Conferences, 2024)
The flexible and efficient production of precise optical free-form surfaces requires advanced kinematic operating principles. Due to the complex surface geometries, polishing processes with point or linear contact are used. These generally result in longer polishing times due to the smaller footprint compared to large-area polishing tools. The creation of a high precision, polishable surface in the shaping steps of the process chain is therefore of great importance. This applies in particular to minimising the roughness, but also the depth of SSD (sub-surface damage) and the mid-spatial frequency errors before the polishing process. The article describes selected process chains for the production of free-form optics and presents options for optimising the required polishing steps.